Cortical network dynamics are coupled with cognitive aging in rats. Issue 12 (23rd July 2019) - Myrum, Craig; Rossi, Sharyn L.; Perez, Evelyn J.; Rapp, Peter R.
ABSTRACT: Changes in neuronal network activity and increased interindividual variability in memory are among the most consistent features of growing older. Here, we examined the relationship between these hallmarks of aging. Young and aged rats were trained on a water maze task where aged individuals reliably display an increased range of spatial memory capacities relative to young. Two weeks later, neuronal activity was induced pharmacologically with a low dose of pilocarpine and control animals received vehicle. Activity levels were proxied by quantifying the immediate early gene products Arc and c‐Fos. While no relationship was observed between basal, resting activity, and individual differences in spatial memory in any brain region, pilocarpine‐induced marker expression was tightly coupled with memory in all areas of the prefrontal cortex (PFC) and hippocampus examined. The nature of this association, however, differed across regions and in relation to age‐related cognitive outcome. Specifically, in the medial PFC, induced activity was greatest in aged rats with cognitive impairment and correlated with water maze performance across all subjects. In the hippocampus, the range of induced marker expression was comparable between groups and similarly coupled with memory in both impaired and unimpaired aged rats. Together the findings highlight that the dynamic range of neural network activity across multiple brain regions is a critical component of neurocognitive aging.